Effect of Information Quality, Social Psychological Distance, and Trust on Consumer Purchase Intentions on Social Commerce Shopee - Hidayat, Anas (Archives of Business Research, 2022)
This study aims to determine how the influence of information quality, social psychological distance, trust on consumer purchase intentions on e-commerce shopee. The test in this study used 202 respondents. The sampling technique used in this research is purposive sampling. This study uses the Structural Equation Modeling (SEM) Analysis tool which was developed to test the research hypotheses processed using the AMOS version 24 program. The data variables used in this study are the quality of information, social psychological distance, trust and consumer purchase intentions, these variables form four hypotheses. And the results of the analysis in this study indicate that the quality of information has a positive effect on social psychological distance, the quality of information has a positive effect on trust, Social psychological distance has a positive effect on trust, Trust has a positive effect on purchase intention.